Sciatic nerve schwannoma complicated by nerve bundle membrane effusion: Two case reports and a literature review - He, Lian; Zhang, Yan-Ji; He, Shi-Li; Zhang, Jia-Ren; Wu, Jun; Zhang, Gao-Feng; Wang, Da-Li (Frontiers in Oncology, 2022)
Schwannoma is a benign tumor that originates from Schwann cells in the peripheral nerve tunica or bundle of nerves and grows along the longitudinal axis of the nerve. Schwannoma can occur in multiple anatomic locations but rarely in the sciatic nerve. To our knowledge, there are no previous reports in the literature related to schwannoma combined with effusion of the nerve bundle membranes. Here, we report two cases of sciatic nerve schwannoma combined with nerve bundle membrane effusion, and the relationship between them is uncertain. We have boldly speculated about this uncertain relationship by combining the two patients’ imaging manifestations to help determine the mechanism of schwannoma or effusion generation as well as a clinical treatment.